Penerapan Metode Moora Pada Penilaian Kinerja Tenaga Pegawai Honorer Pada Dinas Ketenagakerjaan - Juni Irna Purba; Muhammad Safii; Iin Parlina (LPPM STIKOM Tunas Bangsa, 2019)
The performance assessment of honorary staff at the Manpower Office was conducted on 7 employees. Aiming to carry out performance appraisals in order to help the office or agency to be able to determine the appropriate employees to be elected if there is an appointment that is carried out once in 4 years, then it is carried out for the assessment of the performance of honorary employees. Then we need a system that can help make a decision to assess the performance of honorary staff as a reasonable basis for 4 years in the future to be able to submit an appointment file based on the criteria and the weight value of each predetermined criterion such as, 35% Attendance, 20% Work Quality, Work Discipline 20%, Service 25%. So that the ranking results that have been processed using the MOORA algorithm, namely, A1: 0.4139 are eligible to be selected in the performance assessment of the highest number of honorary staff. And A3: 0.4103, A2: 0.4042 and so on.